Erratum to: Methods of Electron Microdiffraction and X-Ray Analysis in Structure Study of Nanodisperse Partially Stabilized ZrO2 Powders - Zaporina, N. A.; Doynikova, O. A.; Krumina, A. P.; Grabis, J. P.; Bocharov, Dmitry V. (Pleiades Publishing, 2019)
Analytical electron microscopy (AEM) has been used to study both structure and morphology of partially yttria-stabilized zirconia dioxide nanopowders (YSZ) obtained by wet-chemical methods (glycine and azeotropic distillation) and ceramics produced from them. Both morphological and structural inhomogeneity of nanopowders obtained by glycine (glc) method has been estimated. Besides the tetragonal ZrO2 phase (results of X-ray analyses) the cubic phase of ZrO2 with different degree of crystallinity has been estimated by Electron Microdiffraction (EMD) methods. In powders obtained by azeotropic distillation (dest) method besides the amorphous phase (identified in X-ray investigations) the high disperse cubic zirconia phase has been identified using high local EMD method. It has been detected the yttrium influence on the degree of crystallinity in nanopowders obtained by azeotropic distillation method without yttria (dest-0YSZ) and with 5 wt % Y2O3 (dest-5YSZ). It has been determined the difference in ceramic morphology produced from these powders. Ceramics mode of nanopowders containing yttria (glc-5YSZ and dest-5YSZ) have a homogeneous surface which consists of different size globules (0.1–0.6 μm) and contains some little pores (∼370 nm). Ceramics mode of nanopowders without yttria have inhomogeneous surface with numerous cracks. Separate parts of the latter ceramics consist of globules, their sizes are of 0.2–0.5 μm.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics